Current Global Economic Crisis In India: Impact of Global Economic Crisis on India's Financial Sector (Journal of Advances and Scholarly Researches in Allied Education, 2014)
India’s financial sector is not deeply integrated withthe global financial system, which spared it the first round adverse effects ofthe global financial crisis and left Indian banks mostly unaffected. However,as the financial crisis morphed in to a full-blown global economic downturn,India could not escape the second round effects. The global crisis has affectedIndia through three distinct channels: financial markets, trade flows, andexchange rates. The Subprime Mortgage Crisis is an ongoing economicproblem that has become more apparent in 2008 and has resulted in reducedliquidity in the global credit market and also the banking & financialsystems. This crisis has exposed the weakness in the global financial systemand also the regulatory framework that is overlooking them.